2015
DOI: 10.18805/lr.v38i5.5952
|View full text |Cite
|
Sign up to set email alerts
|

Participatory appraisal of production constraints, preferred traits and farming system of cowpea in the northern Namibia: implications for breeding

Abstract: Cowpea [<italic>Vigna unguiculata</italic> (L.) Walp.] productivity is low in the subsistence farming systems due to biotic, abiotic and socio-economic constraints. The objective of this study was to assess farmers’- perceived production constraints, preferred traits and the farming system of cowpea, and its implication for breeding in northern Namibia. A participatory rural appraisal studies was conducted across four selected regions of northern Namibia including Kavango East, Kavango West, Oshiko… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(57 citation statements)
references
References 11 publications
10
47
0
Order By: Relevance
“…In Namibia and other arid and semi-arid regions of sub-Saharan Africa, farmers prefer short cycle duration cowpea varieties which mature within 55 to 60 days after planting (Abadassi, 2015;Horn et al, 2015). In the present study, the genotype R1P12 (Nk100) was found to be the most promising early maturing variety favourably rated by 59.7 percent per cent of participating farmers (Table 4).…”
Section: Drought Tolerancementioning
confidence: 52%
See 4 more Smart Citations
“…In Namibia and other arid and semi-arid regions of sub-Saharan Africa, farmers prefer short cycle duration cowpea varieties which mature within 55 to 60 days after planting (Abadassi, 2015;Horn et al, 2015). In the present study, the genotype R1P12 (Nk100) was found to be the most promising early maturing variety favourably rated by 59.7 percent per cent of participating farmers (Table 4).…”
Section: Drought Tolerancementioning
confidence: 52%
“…Most participating farmers (79 percent) selected the genotype R11P11 (Bi450) as the most suitable candidate with a very good and larger pod size (Table 4). In Namibia, farmers prefer larger pod size bearing > 10 grains per pod (Horn et al, 2015). Similarly, most farmers in the study areas preferred larger grain sizes of cowpea (Horn et al, 2015).…”
Section: Drought Tolerancementioning
confidence: 73%
See 3 more Smart Citations